Evaluation of the Satisfaction and Expectation Levels of the Orthodontic Patients with Their Orthodontic Treatment - Saad Bin Sohail, Anum Tariq, Muhammad Saad Ui Hasan, Ammad Jawed, Waheed Gul Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The success of orthodontist treatment lies in the satisfaction and expectation levels of the patients. There is a need to explore factors which determine the expectation and satisfaction levels of the patients. Objective: The study aimed to analyze the satisfaction level and expectations of orthodontic patients with their orthodontic treatment. Study design: This cross-sectional and observational study was conducted at dentistry department of Islamic International Medical and Dental College Islamabad. The duration of the study was six months from Jan 2022 to June 2022. Material and Methods: The 210 patients that visited orthodontic department of the hospital were selected for analysis. Among those 210 patients, there were 170 females and 40 males. The participants were fully aware of the study and written consent was taken from the patients. The satisfaction level was analyzed. It was observed that there were 16% participants that were unsatisfied. There were 176 patients that were satisfied with the orthodontic treatment they were given. There was no significant co-relation found between people of different age groups (p=0.5). The study was carried out to find features like ethics, behavior and the degree of orthodontist that did the treatment. The comparisons of groups with the orthodontic treatment was carried out and the satisfaction of the patients post-treatment. Results: It was observed that 16% participants were unsatisfied it included 7 males and 27 females. Among the 210 patients that participated there were 176 patients that were satisfied with the orthodontic treatment they were given. There was no significant co-relation found between people of different age groups (p=0.5). There were 70% patients that reported that they had no problem during the treatment. And there were 30% patients that felt problems. There were many problems described by the patients. Conclusion: The study reported that majority of the patients significantly met their expectations of the treatment. There was no orthodontic treatment linked factor that had significant association on the satisfaction of the patients. Keywords: Orthodontic patients, satisfaction level and degree of orthodontist.